Penggunaan teknologi sonic bloom untuk meningkatkan produktivitas beberapa varietas tanaman kedelai (Glycine max (L.) Merril): The use of sonic bloom technology to increase the productivity of several soybean plant varieties (Glycine Max (L.) Merril) - Pujiwati, Istirochah; Sholihah, Anis (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Soybean is one of the main sources of vegetable protein. Seventy percent of the soybean needs in Indonesia is still imported, due to the low crop productivity and the declining area of soybean planting. Sonic bloom technology is an alternative to increase soybean productivity. This study aims to determine the pattern of the relationship between foliar fertilization intervals in the use of sonic bloom technology with soybean varieties. Method: The research used a factorial experiment using a randomized block design (RBD). The first factor is the interval of using sonic bloom, I5: 5-day interval, I10: 10-day interval, and I15: once every 15 days. The second factor was soybean varieties, VA: Anjasmoro, VD: Dega-1, and VM: Mallika (black soybean). The data obtained were analyzed for Analysis of Variance with the FÎ± = 0.05 test followed by the 5% Honest Significant Difference (HSD) test and correlation regression analysis.The results showed that different soybean varieties have different responses to plant length, number of leaves and leaf area at different intervals of sonic bloom exposure. Result: Soybean plants with thicker hairs (trichomes) such as the Dega-1 variety require the use of sonic bloom technology with shorter intervals compared to varieties with sparse hairs such as Anjasmoro and Mallika black soybeans. Conclusion: The use of sonic bloom technology was able to increase the productivity of soybean varieties Anjasmoro, Mallika and Dega-1 each by 68.3%; 48.3% and 10.5%.